The effect of prestressing force on natural frequencies of concrete beams – A numerical validation of existing experiments by modelling shrinkage crack closure - Gan, Bing-Zheng (2019)
This paper investigates the effect of prestressing force on the natural frequencies of reinforced concrete beams. From a pure theoretical point of view, such effects in different prestressing conditions appear to involve no ambiguity; however, in practice contradictory observations have been reported in existing research publications. Theoretical studies showed that natural frequencies would be decreasing or unchanged in different scenarios. On the other hand, some experiments that were conducted on prestressed concrete beams indicated an increasing trend of the natural frequencies with the prestressing force. This paper is aimed to provide a systematic explanation of the reasons causing the discrepancies and propose a coherent framework for the prediction of the natural frequencies under a prestressed condition. Numerical simulations using finite element model are carried out to simulate the influence of prestressing force on natural frequencies with the existence of the shrinkage cracks. The results demonstrate that such shrinkage-type cracks inside the concrete indeed tend to close when the prestressing force is applied, and this in turn increases the bending stiffness and consequently results in an increase of the natural frequencies of the beams.